1331 Finding at-risk, low wage workers in community health centres in the us. (24th April 2018) - Forst, Linda; Topete, Liza; Zanoni, Joseph; Friedman, Lee
Abstract : Introduction: The 'working poor' bear an inequitable burden of work-related injuries, illnesses, and fatalities. They often obtain healthcare in community health centres (CHCs) and do not report work-relatedness. The aim was to determine whether the CHCs are a high yield venue for reaching low wage workers and to examine low-wage workers' experience with Workers' Compensation (WC). Methods: A mixed methods survey was conducted in rural and urban CHCs. Results: 50 interviews among largely Latino and African-American workers from 11 different sectors and 41 different job titles, most of them associated with low wages, showed: 55% had experience with a work-related; all knew the employer was responsible for health care. Most respondents did not access their full rights. The major reporting barriers were fear of job loss, fear of deportation, and personal stoicism. Knowing one's rights and finding an advocate were noted facilitators of reporting. Discussion: Lack of reporting circumvents the use of WC, depriving these patients of optimal healthcare and limiting access to medication, rehabilitation, disability compensation and wage replacement. Furthermore, it shifts the burden of fee reimbursement to CHCs, federal programs, and the worker-patients. Fear of job loss and deportation of adds to the list of rights infringement and root causes of health inequities. Increasing knowledge of labour laws and health and safety protections should improve health outcomes. Low-wage, at-risk, and formerly injured workers were easy to find in a CHC, suggesting that this as a venue for training of workers and of primary care providers. Policy initiatives to protect these workers are critical.